2016
DOI: 10.1002/nbm.3472
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Choline/Creatine and Apparent Diffusion Coefficient values with the prognostic parameters of Head and Neck Squamous Cell Carcinoma

Abstract: The aim of this study was to measure choline/creatine (Ch/Cr) levels through (1)H-MRS and apparent diffusion coefficient (ADC) values through diffusion-weighted MRI, and to correlate these values with the prognostic parameters of head and neck squamous cell carcinoma (HNSCC). The institutional review board approved this study and informed written consent was obtained from all study participants. A prospective study of 43 patients (31 men and 12 women; mean age, 65 years) with HNSCC was conducted. Single-voxel … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(27 citation statements)
references
References 37 publications
0
27
0
Order By: Relevance
“…First, this study used diffusion-weighted MR imaging. Further studies with multi-parametric MR imaging [26][27][28][29][30][31][32][33][34] with reduced volume of view and monitoring the patients after therapy [35,36] are needed in the future. Second, ROI was applied for calculation of the ADC value.…”
Section: Discussionmentioning
confidence: 99%
“…First, this study used diffusion-weighted MR imaging. Further studies with multi-parametric MR imaging [26][27][28][29][30][31][32][33][34] with reduced volume of view and monitoring the patients after therapy [35,36] are needed in the future. Second, ROI was applied for calculation of the ADC value.…”
Section: Discussionmentioning
confidence: 99%
“…Third, this study applies diffusion-weighted imaging on 1.5-Tesla scanners. Further studies applied to diffusion tensor imaging combined with other sequences of MR such as arterial spin labelling on higher 3-Tesla scanners will improve the results in the future [35][36][37][38][39][40][41][42][43][44][45][46].…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, studies by Razek have shown that ADC metric has a prognostic value in HNSCC[29-31]. They reported a mean ADC value in nasopharyngeal carcinoma (NPC) of 0.99 ± 0.11 × 10 -3 mm 2 /s.…”
Section: Discussionmentioning
confidence: 99%
“…In a separate study by the same group, it was reported that the mean ADC value of residual or recurrent lesions (1.17 ± 0.33 × 10 -3 mm 2 /s) was less than that observed in post-therapeutic changes (2.07 ± 0.25 × 10 -3 mm 2 /s)[30]. They also showed that ADC values with metabolic ratio (Ch/Cr) obtained from 1H-MRS are well correlated with several prognostic parameters of HNSCC[31]. …”
Section: Discussionmentioning
confidence: 99%